PENENTUAN UMUR SIMPAN METODE ACCELERATED SHELF-LIFE TESTING (ASLT) PADA KOSENTRAT IKA GABUS (Ophiocepahlus striatus) DALAM KAPSUL - Julyaningsih, Andi Hermina; Mansyur Hamdani, Ibnu; Bakar Tawali, Abu (Jurnal Agritechno, 2024)
Concentrated albumin from snakehead fish can be made into a powder form and then packed in capsules which can be as a food supplement for the human body. Concentrated albumin in capsule is considered more efficient and economical to fulfill the body's need for albumin mainly for people suffering from degenerative disease. Determination of the shelf life of the product in addition to a guarantee the safety food product for consumers can also help producers and distributors to distribute their products. Determination of the shelf life can be a reference to the manufacturer or distributor when a product should be circulated and withdrawn from the market. Methods in determining the shelf life of the snakefish concentrate in capsule is using the Arrhenius equation. Products were stored in three different temperature, The ambient temperature (28 0C) and two extreme temperatures (43 0C and 530C). The parameters were the total microbial, TBA value, albumin, moisture content, ash content and organoleptic includes appereance and texture. Experimental design was a complete randomized design (CRD) with one factor is temperature. Based on the chemical analysis which was TBA as the key parameter, the shelf life of snakehead fish concentrate in capsule was 217 days or 7 months, while from the physical analysis (organoleptic) that appearance as a key parameter, the shelf life of the snakehead fish concentrate in a capsule was 367.6 days or 12.3 months.